Studi Geologi Daerah Bukit Harapan Kecamatan Bua Kabupaten Luwu Provinsi Sulawesi selatan - Abdul Rizal Muladi; Aang Panji Permana; Ninasafitri Ninasafitri (Universitas Negeri Gorontalo, 2026)
This study aims to examine the geological conditions of the Bukit Harapan area, Bua District, Luwu Regency, South Sulawesi. The study focuses on geomorphological, stratigraphic, and geological structural aspects based on field mapping data. The methods used include direct observation, geomorphological analysis, and interpretation of field geological data. The results indicate that the study area is composed of denudational hill geomorphological units and alluvial plains. Stratigraphically, the area consists of a gabbro unit as the oldest rock unit and alluvial deposits as the youngest unit. The geological structure developed in the area is represented by joints (tension joints), reflecting the influence of regional stress. These geological conditions demonstrate the relationship between lithology, geomorphic processes, and geological structures in shaping the landscape of the study area.